2013
DOI: 10.1089/ast.2013.1034
|View full text |Cite
|
Sign up to set email alerts
|

Raman Hyperspectral Imaging of Microfossils: Potential Pitfalls

Abstract: Initially, Raman spectroscopy was a specialized technique used by vibrational spectroscopists; however, due to rapid advancements in instrumentation and imaging techniques over the last few decades, Raman spectrometers are widely available at many institutions, allowing Raman spectroscopy to become a widespread analytical tool in mineralogy and other geological sciences. Hyperspectral imaging, in particular, has become popular due to the fact that Raman spectroscopy can quickly delineate crystallographic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…Previous studies have noted that this method can be problematic if materials contain Raman bands in similar locations, for example the haematite 1320 cm −1 band and the ‘D’ band in carbonaceous material (Marshall et al . , Marshall and Marshall , Marshall and Olcott Marshall ). As a result, it has been suggested that intensity images representing the ‘G’ band at 1600 cm −1 should be used to identify carbonaceous material (Marshall and Marshall ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have noted that this method can be problematic if materials contain Raman bands in similar locations, for example the haematite 1320 cm −1 band and the ‘D’ band in carbonaceous material (Marshall et al . , Marshall and Marshall , Marshall and Olcott Marshall ). As a result, it has been suggested that intensity images representing the ‘G’ band at 1600 cm −1 should be used to identify carbonaceous material (Marshall and Marshall ).…”
Section: Resultsmentioning
confidence: 98%
“…, Smith and Godard , Zinin et al . , Marshall and Olcott Marshall ). Because fifth‐order polynomials' baseline correction has been widely used on hyperspectral data sets a priori and linear models were the most common in geological studies, a hyperspectral data set from the Apex chert was baseline‐corrected using linear and fifth‐order polynomials with two different mask region scenarios (Table ).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Among all the possible spectroscopic methods to study the primitive IOM in the context of the origin of life, Raman spectroscopy is one of the most emblematic one, since its first use in paleobiology in the seventies [19,20]. This technique is now sufficiently mature so that ESA/NASA ExoMars planetary mission (proposed for launch in 2018) will contain a miniaturized Raman spectrometer [21].…”
Section: Introductionmentioning
confidence: 99%
“…This technique is now sufficiently mature so that ESA/NASA ExoMars planetary mission (proposed for launch in 2018) will contain a miniaturized Raman spectrometer [21]. However, in addition to some pitfalls such as autofluorescence and laser heating of IOM by the incident laser beam, the latter is highly absorbed by the brown or dark rocks containing carbon (usually cherts), so that Raman spectroscopy is limited to the surface, and 3D Raman hyperspectral imaging is limited to depth smaller than 20 μm in samples [20]. In the perspective of combining complementary techniques for the analysis of fossilized IOM, EPR spectroscopy presents interesting characteristics that are not shared with other techniques.…”
Section: Introductionmentioning
confidence: 99%